2020
DOI: 10.22331/q-2020-06-18-282
|View full text |Cite
|
Sign up to set email alerts
|

A two-player dimension witness based on embezzlement, and an elementary proof of the non-closure of the set of quantum correlations

Abstract: We describe a two-player non-local game, with a fixed small number of questions and answers, such that an ϵ-close to optimal strategy requires an entangled state of dimension 2Ω(ϵ−1/8). Our non-local game is inspired by the three-player non-local game of Ji, Leung and Vidick \cite{ji2018three}. It reduces the number of players from three to two, as well as the question and answer set sizes. Moreover, it provides an (arguably) elementary proof of the non-closure of the set of quantum correlations, based on embe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…All these proofs rely on the representation theory of C * -algebras. A relatively simpler proof, using embezzling entanglement [vDH03] and selftesting, is presented in [Col20].…”
Section: Correlations From Finite Vs Infinite Dimensional Quantum Strmentioning
confidence: 99%
“…All these proofs rely on the representation theory of C * -algebras. A relatively simpler proof, using embezzling entanglement [vDH03] and selftesting, is presented in [Col20].…”
Section: Correlations From Finite Vs Infinite Dimensional Quantum Strmentioning
confidence: 99%
“…This result is an improvement over [6] that shows this separation for larger parameters (n A , n B , m A , m B ) = (5, 6, 3, 3), but is not comparable to [9,14].…”
Section: Introductionmentioning
confidence: 77%
“…This result then improved in [9] and [14] for the parameters (n A , n B , m A , m B ) = (5, 5, 2, 2). Later, Coladangelo [6] gave a quite simple proof of this separation based on the ideas of self-testing and entanglement embezzlement [21]. Coladangelo's proof of C qs = C qc although simpler, is for the parameters (n A , n B , m A , m B ) = (5,6,3,3) and does not improve the parameters of any of the previous results.…”
Section: Introductionmentioning
confidence: 96%
“…Such works have also shown that answering foundational questions about the theory of entanglement is not only of theoretical significance, but brings forward important insights that result in potential applications in quantum information protocols, for example in the certification of high-dimensional entanglement 16,25,26 or high-dimensional states and measurements 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In a related line of work, Slofstra 12 , and the subsequent [13][14][15][16] , provide non-local games which require arbitrarily highdimensional strategies to attain arbitrarily close to optimal winning probabilities. However, for each of these games, any sequence of ideal strategies approaching the optimal winning probability does not have a well-defined limit, and the optimal correlation cannot be attained exactly (not even in infinite dimensions).…”
mentioning
confidence: 99%